Baseline characteristics predicting clinical outcomes and serious adverse events in middle-aged hypertensive women: a subanalysis of the SPRINT in women aged < 65 years - AKICI, AHMET; FAK, ALİ SERDAR; AKMAN, MEHMET (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2020)
Background/aim: The predictability of clinical outcomes in hypertension in specific patient groups, especially underrepresented populations is the key to rational treatment. This study aimed to investigate the impact of baseline characteristics of <65-year-old hypertensive women with an increased risk of cardiovascular events, managed with standard- or intensive-approach, on their clinical outcomes and serious adverse events (SAEs). Materials and methods: Baseline characteristics of <65-year-old hypertensive women (n = 1247) in SPRINT, a multicenter randomized trial to compare standard and intensive antihypertensive treatment, were analyzed with Cox-regression method to determine potential predictors of the clinical outcomes and SAEs. The primary outcome was the composite of myocardial infarction (MI), non-MI acute coronary syndrome, stroke, heart failure, or cardiovascular death. Results: The primary outcome occurred in 3.1% and SAEs in 27.6% of the population. The treatment groups were similar in terms of the primary outcome, SAEs, or their individual components. The primary outcome occurred significantly more in current smokers vs. nonsmokers (HR: 2.85, 95% CI: 1.34-6.09). The subjects who were on aspirin in the intensive-group were significantly more likely to develop the primary outcome (HR: 3.17, 95% CI: 1.23-8.19) and MI (HR: 10.15, 95% CI: 1.19-86.88) compared with those not using aspirin. The risk of overall SAEs was significantly higher in blacks vs. nonblacks (HR: 1.27, 95% CI: 1.01-1.58), in current-smokers vs. nonsmokers (HR: 1.59, 95% CI: 1.23-2.05), and those with vs. without chronic kidney disease (CKD), (HR: 1.38, 95% CI: 1.08-1.77). The likelihood of SAEs significantly increased with age (HR: 1.04, 95% CI: 1.01-1.07). Conclusion: Smoking, aspirin, CKD, black race, and age seemed as important baseline characteristics in follow-up of <65-year-old hypertensive women, also depending on therapeutic strategy. Clinicians are expected to consider these critical parameters for effective antihypertensive management that promotes better outcomes in this middle-aged female population.
Keywords: Hypertension; middle-aged women; intensive pharmacotherapy; cardiovascular; events; SYSTOLIC BLOOD-PRESSURE; CARDIOVASCULAR RISK; SEX-DIFFERENCES; DRUG-REACTIONS; HEART-DISEASE; OBESITY; SMOKING; TRIAL; MEN; PATHOGENESIS